PROSPEK PENGGUNAAN MESIN PANEN PADI COMBINE HARVESTER DI DESA KARANG MULYA SEMENDAWAI TIMUR OKU TIMUR - Sudarti (Jurnal Bakti Agribisnis, 2016)
The purpose of this study is to: (1) To calculate the cost, revenue and income obtained from the use of Combine Harvester rice harvesting machine in Karang Mulya Village, East Semendawai District, OKU Timur Regency, (2) To analyze the feasibility of using Combine harvest machine Harvester in Karang Mulya Village, East Semendawai Sub-district, OKU Timur Regency, (3) To know the prospect of Harvesters Combine Harvester harvesting machine in Karang Mulya Village, East Semendawai District, especially in East OKU Regency. The research will be conducted in Karang Mulya Village, East Semendawai District, OKU Timur Regency. Determination of the location is deliberately determined because in the village of Karang Mulya most of the population work as rice farmers. When harvest season comes the farmers are constrained by the limited labor harvest so that there are respondents who took the initiative to seek the harvesting machine harvesting rice harvester. The research will be conducted in March 2015. The study found that the total production cost incurred by the respondents in the Harvesting Combine Harvester harvesting machine business in Karang Mulya Village amounted to Rp 871,710,000, the business income was Rp 1,107,270,000 so the income received was Amounting to Rp 235,560,000. Harvesting machine harvesting Combine Harvester in Karang Mulya village feasible financially to be developed, it can be known from the calculation of business NPV value of Rp 109,848,197, IRR value is 58.10% and Net B/C value of 1,52.